ATTITUDE OF HIGH SCHOOL STUDENTS TOWARDS MULTIMEDIA - C, Sumathi; Vijayarani , K. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present study is to study the attitude of the high school students towards using multimedia in learning process. The study focusses on the high school student’s attitude in learning science through the use of multimedia aided classroom. The samples selected from the population of high school students is about 70 using random sampling method. Survey method is adopted in collecting the data using the multimedia attitude scale (MAS). The instrument was constructed and standardized by undergoing the total internal correlation method and thus by discarding the items with lower correlation. Thus the initial draft of the MAS consists of 40 items and final draft of the tool consist of 35 items after removing 5 items with lower inter-correlation value and modifying 5 items which had r value between 0.02 to 0.26. The study revealed that the there is a favorable attitude among the high school students towards the use of multimedia in learning process.